2015
DOI: 10.2176/nmc.oa.2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Specific Shrinkage of Carotid Forks in Moyamoya Disease: A Novel Key Finding for Diagnosis

Abstract: This study was aimed to analyze the outer diameter of the involved arteries in moyamoya disease, using three-dimensional (3D) constructive interference in steady state (CISS) and direct surgical inspection. Radiological evaluation was performed in 64 patients with moyamoya disease. As the controls, six patients with severe middle cerebral artery (MCA) stenosis and 17 healthy subjects were also recruited. On 3D-CISS, the outer diameter was quantified in the supraclinoid portion of internal carotid artery (C1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Kaku et al [ 21 ] proposed the constrictive remodeling theory that the outer diameter narrowing of the affected intracranial major arteries was the early characteristic of MMD, as demonstrated by three-dimensional (3D) constructive interference in steady-state (CIISS) MR imaging. Similar observation on 3D CIISS MR imaging in the diagnosis of MMD was reported by Kuroda and colleagues [ 27 ]. Ryoo and colleagues [ 31 ] reported that MMD was characterized by concentric enhancement on distal ICA and shrinkage of MCA, while atherosclerosis represented focal eccentric enhancement at the symptomatic segment of intracranial arteries.…”
Section: Diagnosis Of MMDsupporting
confidence: 87%
“…Kaku et al [ 21 ] proposed the constrictive remodeling theory that the outer diameter narrowing of the affected intracranial major arteries was the early characteristic of MMD, as demonstrated by three-dimensional (3D) constructive interference in steady-state (CIISS) MR imaging. Similar observation on 3D CIISS MR imaging in the diagnosis of MMD was reported by Kuroda and colleagues [ 27 ]. Ryoo and colleagues [ 31 ] reported that MMD was characterized by concentric enhancement on distal ICA and shrinkage of MCA, while atherosclerosis represented focal eccentric enhancement at the symptomatic segment of intracranial arteries.…”
Section: Diagnosis Of MMDsupporting
confidence: 87%
“…Kuroda et al demonstrated the specific shrinkage of the involved arteries in MMD by using 3D constructive interference in steady state (CISS) and direct surgical inspection. 25) On the other hand, a twig-like MCA should already have been formed at birth, if the hypothesis that the twig-like MCA is the persistent fetal arterial network, is correct. If an infant with a twig-like MCA is found, the hypothesis is persuasive.…”
Section: Anomalies Of the Mcamentioning
confidence: 99%
“…Histopathological findings in the carotid terminations include fibrocellular thickening of the intima, irregular waving of the internal elastic lamina, and attenuation of the media, all contributing to the progressive luminal stenosis ("shrinkage") in the carotid fork. However, it has also been demonstrated that the outer diameter simultaneously decreases, as opposed to atherosclerotic degeneration [27,28].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In addition, "indirect symptoms" likely caused by the aberrant collateralization have been described. Migraine-like (with or without aura) and tension-type-like headache attacks have been reported in up to 50-70% in different series of Eastern and Western MMA patients [3,4,[27][28][29][30][31]37]. Headache, which has been supposed to be due to collateralization processes and stimulation of dural nociceptors by dilated transdural collaterals, was also associated with brain hypoperfusion [40].…”
Section: Clinical Featuresmentioning
confidence: 99%